Tools for self- or peer-assessment of interprofessional competencies of healthcare students: a scoping review - Brownie, Sharon; Yap, Jia Rong; Blanchard, Denise; Amankwaa, Issac; Pearce, Amy; Sampath, Kesava Kovanur; Yan, Ann-Rong; Andersen, Patrea; Broman, Patrick (Frontiers in Medicine, 2024)
Running Head: Healthcare student self-assessment of interdisciplinary competencies.Introduction: Healthcare professionals are expected to demonstrate competence in the effective management of chronic disease and for long-term health and rehabilitation needs.Care provided by groups of collaborating professionals is now well recognized as a more effective way to support people living with these conditions than routine, single profession clinical encounters. Clinical learning contexts provide hands-on opportunity to develop the interprofessional competencies essential for health professional students in training, however, suitable assessment tools are needed to support student attainment of interprofessional competencies with self-assessment espoused as an important component of learning.Method: A structured approach was taken to locate and review existing tools used for the self-assessment and peer-assessment of students' competencies relevant to interprofessional practice.Results: A range of self-and/or peer-assessment approaches are available including formally structured tools and less structured processes inclusive of focus groups and reflection.Discussion: The identified tools will usefully inform discussion regarding interprofessional competency self and peer-assessment options by healthcare students participating a broad range of clinical learning contexts. Conclusions: Self-and/or peer-assessment is a useful approach for those seeking to effectively enhance interprofessional learning and measure attainment of related competencies.